INFRASTRUKTUR TEKNOLOGI INFORMASI UNTUK MENDORONG KNOWLEDGE SHARING INTENTION: STUDI KASUS SISTEM RUMAH SAKIT - Florencia Judith Widyarini; Yoke Pribadi; Angela Caroline; Agus Gunawan (Business Administration Department - Universitas Katolik Parahyangan, 2022)
The COVID-19 pandemic is forcing hospitals to share knowledge more frequently, so that medical staff have adequate capabilities to better treat patients. One of the tools that can support knowledge sharing activities is the availability of adequate information technology infrastructure. This study will describe the influence of hospital information technology infrastructure on knowledge sharing intention. This study uses quantitative methods with a purposive sampling technique. The data obtained were 45 employee respondents in the finance bureau and the procurement and logistics bureau at St. X Hospital. The results showed that the procedure dimension had the highest score and the network dimension had the lowest score in the information technology infrastructure variable. As for the knowledge sharing intention variable, the proximity dimension has the highest score and the type of knowledge has the lowest score. The results of the study which show that information technology infrastructure does not affect knowledge sharing intention, make the hospital must be able to fix an information technology infrastructure before continuing its development. One of them is by giving awards to employees who are active and regularly use information technology infrastructure facilities especially as a medium to share knowledge.